1994
DOI: 10.1097/00000658-199410000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Meckelʼs Diverticulum An Epidemiologic, Population-Based Study

Abstract: ObjectiveThe authors determined whether Meckel's diverticulum, discovered incidentally at operation, should be removed. Summary Background DataIt is not clear from the medical literature whether the risk of an incidental Meckel's diverticulectomy is greater than the risk of leaving the diverticulum in place. MethodsThe authors used the medical experience of Olmsted County, Minnesota residents for the period 1950 to 1992 to answer the question. ResultsDuring the period, 58 residents developed Meckel's complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
239
0
27

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(274 citation statements)
references
References 14 publications
8
239
0
27
Order By: Relevance
“…Failure to obliterate may lead to variety of congenital anomalies including; Meckel's diverticulum, vitelline cord, umbilical sinus, enteric fistula and or haemorrhagic umbilical mass [1][2][3][4]. To date only 15 cases have been reported in the English medical literature [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to obliterate may lead to variety of congenital anomalies including; Meckel's diverticulum, vitelline cord, umbilical sinus, enteric fistula and or haemorrhagic umbilical mass [1][2][3][4]. To date only 15 cases have been reported in the English medical literature [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of these patients was 1.5%, with 7% morbidity; incidental removal had 1% mortality and 2% morbidity. 6 There are several studies stating the safe and effective use of laparoscopy in case of complicated Meckel's diverticulum. 15,16 It can be used in undiagnosed acute abdominal pain, in obstruction and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4] A person with Meckel's diverticulum has a 4-6% lifetime risk of developing a complication 5 with a male to female ratio ranging from 1.8:1 to 3:1. 6 The most clinical presentation is GI bleeding in pediatric age group. Other complications include obstruction, intussusceptions and diverticulitis with perforation occurring rare in less than 7% of patients having complication.…”
Section: Introductionmentioning
confidence: 99%
“…A general rule of 2 is followed: present in 2 % popula on, 2 feet away from ileocaecal valve and 2 inches long although many anatomical varia ons exist. In many cases Meckel's diver culum is asymptoma c. Cullen et al reported in a popula on based study that the life me risk of developing a complica on of Meckel's diver culum was es mated to be 6.4% 3 . The complica ons like painless per rectal bleeding, intes nal obstruc on, diver culi s, persistent vitellointes nal duct fi stula, intussusep on, ulcera on or perfora on may occur 4 .…”
Section: Discussionmentioning
confidence: 99%